Pengaruh Manajemen Laba Dan Ukuran Perusahaan Terhadap Agresivitas Pajak Dengan Komisaris Independen Sebagai Pemoderasi - Ali Ivan Patria; Wulandari Cahyani Putri (CV. ULIL ALBAB CORP, 2024)
This study aims to investigate the influence of earnings management and firm size on tax aggressiveness with independent commissioners as moderators. This research is of the quantitative associative type. The population used in this study consists of 74 companies in the basic and chemical industry sectors. The sampling technique used is purposive sampling, where criteria are determined that are most suitable for this research. Thus, the sample used in this study is 10 companies with a research period of 7 years, resulting in 70 data points being processed. This research uses panel data regression analysis techniques. The results of the research show that earnings management and firm size have simultaneous effects. Partially, earnings management affects tax aggresiveness and firm size affects tax aggresiveness. Furthermore, independent commissioners is unable to moderate earnings management and firm size on tax aggresiveness.